THE IMPACT OF ZIS MANAGEMENT OF LAZNAS AL-AZHAR FOR THE YOUTH IN THE PROGRAM OF RUMAH GEMILANG INDONESIA IN SURABAYA - Nadiyah Bilqis; Irham Zaki (Universitas Airlangga, 2020)
This study aims to determine the impact of LAZNAS Al-Azhar's ZIS fund management in empowering productive youth through the Rumah Gemilang Indonesia program, seen from increased religiosity and increased income. This research uses a qualitative approach with a case study strategy. According to the result, it is showed that the empowerment program was implemented through the Rumah Gemilang Indonesia program by LAZNAS Al-Azhar by receiving funding from donors. The synergy of roles and assistance between LAZNAS Al-Azhar and the fostered participants went very well. The final impact felt is an increase in income and moral improvement. Thus, young people can be free from the problem of unemployment and poverty.Keywords: Productive Zakat, Zakat Institution, Empowerment, UnemploymentREFFERENCE Aziz Syamsudin. (2008). Kaum muda menatap masa depan Indonesia. Jakarta: PT. Wahana Semesta IntermediaBadan Pusat Statistik. (2018). Tingkat pengangguran terbuka. (http://www.bps.go.id diakses 20 Februari 2019).Badan Pusat Statistik. (2018). Statistik pemuda provinsi Jawa Timur 2018. (http://www.bps.go.id diakses 20 Februari 2019).Departemen Agama RI, Qur’an terjemah tajwid, (Jakarta: Maghfirah Pustaka, 2006)Hafidhudhin, Didin. (2002). Zakat dalam perekonomian modern. Jakarta: Gema Insani.Malumbot, R. H. (2015). Program pemberdayaan dalam penanggulangan kemiskinan di Kota Bitung. Politico: Jurnal Ilmu Politik.Permono, Sjechul Hadi. (1992). Sumber-sumber pengelolaan zakat. Jakarta: Pustaka Firdaus.Sugiyono. (2009). Metode Penelitian kuantitatif, kualitatif dan R&D. Bandung: Alfabeta.Undang-Undang Republik Indonesia Nomor 23 Tahun 2011 Tentang Pengelolaan ZakatWebsite Rumah Gemilang Indonesia. (2019). (http://www/rumahgemilang.com, diakses pada 28 Januari 2019).Widiastuti, Tika. (2015). Model pendayagunaan zakat produktif oleh lembaga zakat dalam meningkatkan pendapatan mustahiq.Jurnal Ekonomi dan Bisnis Islam, 1(1), 89-102.Yin, Robert K. (2015). Studi kasus desain dan metode. Jakarta: Rajawali PersZuardi, H.M. (2013). Optimalisasi zakat dalam ekonomi Islam. Adzkiya: Jurnal Hukum dan Ekonomi Syariah, 1(1), 16-34.